2015
DOI: 10.1177/1474515114567035
|View full text |Cite
|
Sign up to set email alerts
|

Person-centred care for patients with chronic heart failure – a cost–utility analysis

Abstract: It must be emphasized, however, that these positive effects, both cheaper and somewhat better, were obtained only among those receiving the PCC intervention in its intended form, PCC(PP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 24 publications
2
96
0
1
Order By: Relevance
“…For example, in chronic conditions such as chronic heart failure (CHF), PCC has been shown to reduce length of hospital stay [5]; reduce uncertainty about the disease [6] and treatment and improve the efficiency of the discharge process [7]; lower healthcare costs [8, 9]; reduce re-hospitalization rates and improve health-related quality of life [10]; and improve adherence to medications [11]. A study evaluating the effects of PCC along the chain of health care in patients with acute coronary syndromes (ACS) showed a three-fold higher chance [12] (even higher when complemented with an eHealth tool [13]), of improved general self-efficacy in combination with return to work or previous activity level without increasing the risk of cardiovascular events or death.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in chronic conditions such as chronic heart failure (CHF), PCC has been shown to reduce length of hospital stay [5]; reduce uncertainty about the disease [6] and treatment and improve the efficiency of the discharge process [7]; lower healthcare costs [8, 9]; reduce re-hospitalization rates and improve health-related quality of life [10]; and improve adherence to medications [11]. A study evaluating the effects of PCC along the chain of health care in patients with acute coronary syndromes (ACS) showed a three-fold higher chance [12] (even higher when complemented with an eHealth tool [13]), of improved general self-efficacy in combination with return to work or previous activity level without increasing the risk of cardiovascular events or death.…”
Section: Introductionmentioning
confidence: 99%
“…PCC has also been shown to produce improved outcomes such as increased security and satisfaction with hospital care, shorter hospital stays, and a more efficient discharge process (Dudas et al, 2013;Ekman, Wolf, et al, 2011;Ulin, Olsson, Wolf, & Ekman, 2016). Other studies report improved self-efficacy (Fors et al, 2015), and reduced costs (Hansson et al, 2016;Sahlen, Boman, & Brännström, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that these actions improve patients' quality of life [2,3] and the discharge process [4] as well as metabolic control and self-efficacy [5,6]. Furthermore, studies show such efforts decrease patients' fatigue [5] and uncertainty [7], which results in lower costs [8,9] due to shorter hospital stays [3,10,11]. Moreover, staff report higher job satisfaction, a friendlier working environment, and reduced conscience stress when person-centred care is implemented [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%